Online Guidance System Design for Smart Greenhouse - Bonde, Glen Mark; Najoan, Meicsy E.I.; Karouw, Stanley D. S. (Universitas Sam Ratulangi, 2021)
An implementation of technology in agriculture is a smart greenhouse. Smart greenhouse can set the condition inside the greenhouse automatically or remotely to provide the optimal environment for the plant we have in the greenhouse to grow. The online accompaniment system for smart greenhouse is a web based application for monitoring and even controlling remotely or automatically the condition inside the smart greenhouse. The parameter of the environmental conditions is controlled by an agricultural expert so the control actions can be done correctly with the help of real time environmental conditions data inside the greenhouse. If the expert decides to run the system automatically, the expert will only control the parameter and the schedule for the system to make an action to keep the environmental condition inside the greenhouse under the boundary which have been set by the expert. If the expert decides to run the system remotely, the expert can manually control the action to be taken inside the smart greenhouse. This application provides a service for the farmer and the agricultural expert to discuss about farming process. The environmental condition in the smart greenhouse data presented in graphs so it can be easy to understand the data.